Commencing the modernization project on the Gila Gravity Main Canal - Noble, Wade, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2005)
The Gila Gravity Main Canal diverts approximately 700,000 acre-feet annually from the Colorado River at Imperial Dam. The canal serves five irrigation and drainage districts, as well as a number of other contractors and domestic areas. It is federally owned and its administrative board is made up of representatives from each irrigation district. The canal currently faces three problems: sedimentation, imprecise flow measurement, and a lack of real-time monitoring capabilities. Planned responses to these problems include dredging, the installation of a Replogle flume, remote monitoring and canal automation systems, and the application of a clay sealant. This project will be funded by a grant from the Border Environment Cooperation Commission (BECC) and a challenge grant through the US Bureau of Reclamation.
Gila Gravity Main Canal
Not digitized by CSUL Digital Services.
Presented during the Third international conference on irrigation and drainage held March 30 - April 2, 2005 in San Diego, California. The theme of the conference was "Water district management and governance."